Hearing Architecture: A Review of Bill Fontana's "Sonic Shadows" - Downey, Chris (Disability Studies Quarterly, 2013)
A blind architect reviews a sound installation at the San Francisco Museum of Modern Art. Since museums are frequently works of art in themselves, the author describes new avenues for architectural appreciation. Key words: Blindness, blind museum access, Bill Fontana, architecture, sonic aesthetics.